2017
DOI: 10.1002/jsfa.8200
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing diet with Manitoba lingonberry juice reduces kidney ischemia‐reperfusion injury

Abstract: This study shows, for the first time, that daily supplementation with lingonberry juice may protect against loss of kidney function induced by IR injury by modulating JNK signalling and inhibiting the subsequent inflammatory response. © 2017 Her Majesty the Queen in Right of Canada. Journal of the Science of Food and Agriculture © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Lingonberry (Vaccinium vitis-idaea L.) is an evergreen dwarf shrub rich in anthocyanins, which has anti-inflammatory, anti-diabetic, and renal protection properties [64,65]. In another study, mice were fed with a high-fat diet (HFD) to induce chronic kidney injury for investigating the effects of lingonberry on CKD.…”
Section: Lingonberrymentioning
confidence: 99%
“…Lingonberry (Vaccinium vitis-idaea L.) is an evergreen dwarf shrub rich in anthocyanins, which has anti-inflammatory, anti-diabetic, and renal protection properties [64,65]. In another study, mice were fed with a high-fat diet (HFD) to induce chronic kidney injury for investigating the effects of lingonberry on CKD.…”
Section: Lingonberrymentioning
confidence: 99%
“…Lingonberry ( Vaccinium vitis‐idaea L.) is a perennial, evergreen dwarf shrub native to northern latitudes and is well known for its high content of anthocyanins and antioxidants compared with other commonly consumed berries (Bakowska‐Barczak et al ., ; Isaak et al ., ). It has been traditionally used in diets not only because it confers the appealing colour to the food, but also because it has been considered as a ‘good for health’ berry rich in vitamins C, A, E and polyphenols (Mane et al ., ; Bujor et al .,; Finnish Food Composition Database).…”
Section: Introductionmentioning
confidence: 97%
“…Certain dietary restrictions are recommended to control the intake of protein, sugar, salt, and fiber content (18). In our previous study, we reported that supplementation of diet with lingonberry juice could protect rats against ischemia-reperfusion-induced acute kidney injury (19). Lingonberry (Vaccinium vitis-idaea L.) is an evergreen dwarf shrub native to North America and Eurasia throughout the Northern Hemisphere (20).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, C-3-Glu is known to improve the redox status, energy, and glucose metabolism in rat kidneys (24). Furthermore, recent studies have revealed that lingonberry exhibits antidiabetic and renal protective properties (19,25). However, its role in CKD has not been identified.…”
Section: Introductionmentioning
confidence: 99%